Penerapan Sistem Manajemen Keselamatan Pertambangan di Tambang Andesit PT. Gunung Kulalet Bandung - Dedi Saputra; Yunus Ashari; Aviasti (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. The application of the Mining Safety Management System (SMKP) in this study has a legal basis for carrying out the orders of the Law of the Republic of Indonesia Number 1 of 1970 concerning occupational safety and health that every worker has the right to protection for his safety in carrying out work for the welfare of life and increase production and productivity Nationally, occupational safety and health is applied to all industries in accordance with the needs of each industry, especially in the mining industry. The application of the Mining Safety Management System (SMKP) is in accordance with the Decree of the Minister of Energy and Mineral Resources Number 1827 K 30 MEM 2018 concerning guidelines for the implementation of good mining engineering principles where the implementation of the Mining Safety Management System (SMKP) is assessed at least once a year audit whether carried out by the party appointed internal or external according to the terms and conditions of applicable law. This research is intended to develop a mining safety management system at PT. Mount Kulalet in accordance with current applicable law, the SMKP assessment approach based on the internal audit matrix for the application of SMKP has a value of 81.6%, included in the minor category, evaluation is needed, adjustments to legal regulations and controls need to be improved. Abstrak. Penerapan Sistem Manajemen Keselamatan Pertambangan (SMKP) dalam penelitian ini memiliki landasan hukum menjalankan perintah Undang-Undang Republik Indonesia Nomor 1 Tahun 1970 tentang keselamatan dan kesehatan kerja bahwasanya setiap tenaga kerja berhak mendapat perlindungan atas keselamatannya dalam melakukan pekerjaan untuk kesejahteraan hidup dan meningkatkan produksi serta produktivitas Nasional, keselamatan dan kesehatan kerja diterapkan pada semua industri sesuai dengan kebutuhan industri masing-masing terutama pada industri pertambangan. Penerapan Sistem Manajemen Keselamatan Pertambangan (SMKP) sesuai dengan Keputusan Menteri ESDM Nomor 1827 K 30 MEM 2018 tentang pedoman pelaksanaan kaidah teknik pertambangan yang baik di mana penerapan Sistem Manajemen Keselamatan Pertambangan (SMKP) dilakukan penilaian minimal audit satu kali dalam satu tahun baik dilakukan oleh pihak internal maupun eksternal yang ditunjuk sesuai syarat dan ketentuan dari hukum yang berlaku. Penelitian ini dimaksud untuk menyusun sistem manajemen keselamatan pertambangan di PT. Gunung Kulalet sesuai dengan hukum yang berlaku saat ini, pendekatan penilaian SMKP berdasarkan matrik audit internal penerapan SMKP memiliki nilai 81,6 % termasuk kedalam kategori minor diperlukan evaluasi, penyesuaian dengan regulasi hukum serta pengendalian yang perlu ditingkatkan.